Distribution and Effects of Estrogen Receptors in Prostate Cancer: Associated Molecular Mechanisms - Ramírez-de-Arellano, Adrián; Pereira-Suárez, Ana Laura; Rico-Fuentes, Cecilia; López-Pulido, Edgar Iván; Villegas-Pineda, Julio César; Sierra-Diaz, Erick (Frontiers in Endocrinology, 2022)
Estrogens are hormones that have been extensively presented in many types of cancer such as breast, uterus, colorectal, prostate, and others, due to dynamically integrated signaling cascades that coordinate cellular growth, differentiation, and death which can be potentially new therapeutic targets. Despite the historical use of estrogens in the pathogenesis of prostate cancer (PCa), their biological effect is not well known, nor their role in carcinogenesis or the mechanisms used to carry their therapeutic effects of neoplastic in prostate transformation. The expression and regulation of the estrogen receptors (ERs) ERα, ERβ, and GPER stimulated by agonists and antagonists, and related to prostate cancer cells are herein reviewed. Subsequently, the structures of the ERs and their splice variants, the binding of ligands to ERs, and the effect on PCa are provided. Finally, we also assessed the contribution of molecular simulation which can help us to search and predict potential estrogenic activities.